Тайна двух зеркал - Городецкая Наталья Геннадьевна (Наталис: Рипол Классик, 2003)
Экземпляры: Д.О. (20200318) / Инвентарный номер: 41081 / Цена: 113.40 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Г 70 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44